Wordsworth's Aeneid and the Influence of its Eighteenth-Century Predecessors. (March 2017) - Widmer, Matthias
Abstract : William Wordsworth's attempt at translating Virgil's Aeneid reached as far as Book 4, and mostly survives in manuscript drafts. The literary influences behind it can be illuminated through the poet's correspondence, and analysed more fully by tracing verbal echoes and other resonances in his translation. Despite the hostility he expressed towards Dryden and Pope, the foremost translators of the previous age, Wordsworth followed them in using heroic couplets, and, as has previously been argued, his translation draws increasingly on Dryden's Aeneis the further he advanced with his project. But Wordsworth owes an equally large debt, hitherto unrecognized, to the eighteenth-century blank verse renderings by Joseph Trapp and others, who anticipated many of his supposed stylistic innovations.